DEVELOPMENT OF ENTREPRENEURSHIP SKILLS AMONG MEDICAL STUDENTS: OPENING BUSINESS OPPORTUNITIES IN THE HEALTH SECTOR - Ayudia, Esa Indah; Denok Tri Hardiningsih; Suzan, Raihanah; Miftahurrahma, Miftahurrahma; Justitia, Budi; Hafizah, Hafizah (Universitas Jambi, 2025)
In the era of globalization and rapid technological advancement, the healthcare sector in Indonesia faces various challenges, including the need for innovation and more effective services. Medical students possess significant potential to contribute to creating relevant solutions for public health issues. However, many of them lack adequate entrepreneurial skills. Conventional teaching methods often fall short in providing students with the practical skills necessary.Therefore, the implementation of Project-based Learning (PjBL) in entrepreneurship courses becomes essential. Through PjBL, students not only learn theory but also engage directly in projects related to current health issues. This allows them to develop practical skills such as market research and business planning. The program involved 119 first-semester medical students, beginning with a Pre-Test to assess their initial knowledge about Community Service, followed by presentation sessions and a Post-Test to evaluate their understanding. Results showed that 60% of students were interested in entrepreneurship within the healthcare sector; 52.5% recognized its importance; however, 70% still lacked an understanding of business concepts in healthcare. A significant increase was observed after the Post-Test was conducted. The application of PjBL needs to be conducted continuously to further enhance students' knowledge about entrepreneurship. Keywords: Entrepreneurship, Project-based Learning (PjBL), Medicine